Multi-Drug Resistant Coliforms in Poultry Meat: A Potential Public Health Concern - Iqbal, Iqra; Iqbal, Muhammad Naeem (PSM Microbiology, 2020)
Poultry flocks are often raised under intensive conditions using large amounts of antimicrobials to prevent and to treat disease, as well as for growth promotion. The wide distribution of antimicrobial-resistant coliforms in the meat and processing environment can play a role in the dissemination of antimicrobial resistance to other pathogenic and commensal bacteria. The high density of multidrug-resistant coliform bacteria in the poultry meat may pose a severe public health risk through related foodborne outbreaks.